Określenie współczynników zamiennych dla drewna wielkowymiarowego kłodowanego sosnowego i świerkowego - Witkowska, Joanna; Jodłowski, Krzysztof (Leśne Prace Badawcze, 2019)
The aim of this paper was to determine conversion factors for stacked pine and spruce logs with a length between 3 and 6 meters. To this end, we measured stacks and their logs for a total of 3,322.12 steres of pine logs and 1,468.46 steres of spruce logs. The conversion factors obtained in this work for pine logs of varying length negatively correlate with log length. However, statistically significant (p